THE EFFECT OF SAFETY SELF-EFFICACY AND SELF-REGULATION ON WORKPLACE ACCIDENTS AMONG THE STAFF OF BOYER AHMAD CITY EDUCATIONAL HOSPITALS - Alamdari, H.; Ahmadizadeh, A. (University of Eloued جامعة الوادي, 2018)
The purpose of this study is to investigate the effect of safety self-efficacy and self-regulation on workplace accidents among the employees of educational hospitals in Boyer Ahmad City. This is a descriptive-correlational research using the field method. It is an applied research in terms of nature and a cross-sectional research in terms of time. The study population consists of the employees of Boyer Ahmad hospitals with a total number of 1494 employees in 2017. A total of 306 employees were selected from the population as the sample size using the Cochran formula. The results showed that self-efficacy and self-regulation variables (promotion focus and prevention focus) influence the work-related accidents. Self-efficacy, self-regulation and prevention focus have negative effects on workplace accidents while promotion focus has a positive impact on it. The results of multiple regression also showed that in total 0.62 percent of occupational accident changes are explained by self-efficacy and self-regulation variables.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: self-regulation, self-efficacy, self-efficacy, promotion focus, prevention focus, workplace accidents